The effectiveness of H. pylori therapy in patients with helicobacter pylori related functional dyspepsia - I. V. Mayev; A. V. Yashina; A. A. Samsonov; D. N. Andreyev; V. B. Grechushnikov; E. E. Pavleeva (Медицинский совет, 2014)
The article presents the results of a study aimed to evaluate the efficacy and tolerability of eradication schemes with macrolides and bismuth in the treatment of patients with Helicobacter pylori related functional dyspepsia (postprandial distress syndrome).